USING GRAPHIC ORGANIZER TO INCREASE STUDENTS’ WRITING PERFORMANCE IN ORGANIZING IDEA - Winda Mayasari (Jurnal Pendidikan Bahasa, 2019)
The development of students' writing skill progresses from arranging some letters to becoming a simple word or phrase, such as writing a name, into a more complex text. This study was undertaken to describe two fundamental purposes related to the use of graphic organizer with eleventh-grade, normal-achieving students: (a) to describe how does Graphic Organizer improve students’ skill in organizing idea and (b) to describe how is the class situation when Graphic Organizer media is implemented in the writing class. The method carried out classroom action research. each procedure took some steps that formed one cycle and this research will be conducted in cycles. Each cycle is going to use Graphic Organizer as teaching media in writing activity. The subjects of the study are 32 students of social classes. Observation, interviews, questionnaires, and diary will be gathered respectively. The discussions on the students' problems in organizing ideas in writing in one side and on the benefits of Graphic Organizer as a solution to help students in organizing ideas in writing in the other side has encouraged the writer to conduct a classroom action research (CAR) on using Graphic Organizer to enhance students' skill in organizing ideas in writing class.Keywords: writing skill, graphic organizer, classroom action research.